Cash Flow Analysis of School Operational Assistance Funds (BOS) at SMA Negeri 9 Seluma - Okta Antonius; Neri Susanti; Novman Ahmad Ali (Journal of Indonesian Management, 2021)
This study aims to describe the Management of Senior High School Operational Assistance Funds (BOS SMA) in SMA Negeri 9 Seluma in 2018; (1) Planning for SMA BOS Funds at SMA Negeri 9 Seluma, (2) Implementation of BOS Funds for SMA Negeri 9 Seluma, (3) Supervision and Evaluation of BOS Funds for SMA at SMA Negeri 9 Seluma, and (4) Reporting on BOS Funds for SMA SMA Negeri 9 Seluma. This research is a qualitative descriptive study. The location for this research is SMA Negeri 9 Seluma, with the research subjects of the Principal, BOS Treasurer, Teachers, and the School Committee. Data collection techniques used are through observation and interviews. The validity of the data in this study with trigulation and membercheck. Data analysis techniques used in the study were: data reduction, data display / presentation, and drawing conclusions and verification. The results showed that (1) Planning for the BOS Fund for SMA Negeri 9 Seluma in 2018 was carried out by compiling RKAS by the school budget team with the knowledge of the School Committee, teachers, employees, and parents of students. The preparation of the RKAS was carried out simultaneously with the preparation of the BOS SMA RAB. (2) Implementation of SMA BOS Funds, the distribution of BOS SMA 2018 Funds in 4 stages. Withdrawal of BOS SMA Funds by the BOS Treasurer. The use of BOS SMA 2018 funds is intended to finance the operational activities of non-operational schools as in the 2018 BOS SMA technical instructions. Publication is carried out by posting a summary of the RKAS on an announcement board and providing a leaflet for the use of BOS SMA funds to student guardians.